Prolonged culturing of colonic epithelial organoids derived from healthy individuals and ulcerative colitis patients results in the decrease of LINE-1 methylation level - Ruta Inciuraite; Ruta Steponaitiene; Odeta Raudze; Ugne Kulokiene; Vytautas Kiudelis; Rokas Lukosevicius; Rasa Ugenskiene; Kestutis Adamonis; Gediminas Kiudelis; Laimas Virginijus Jonaitis; Juozas Kupcinskas; Jurgita Skieceviciene (Scientific Reports, 2024)
Abstract Patient-derived human intestinal organoids are becoming an indispensable tool for the research of digestive system in health and disease. However, very little is still known about the long-term culturing effect on global genomic methylation level in colonic epithelial organoids derived from healthy individuals as well as active and quiescent ulcerative colitis (UC) patients. In this study, we aimed to evaluate the epigenetic stability of these organoids by assessing the methylation level of LINE-1 during prolonged culturing. We found that LINE-1 region of both healthy control and UC patient colon tissues as well as corresponding epithelial organoids is highly methylated (exceeding 60%). We also showed that long-term culturing of colonic epithelial organoids generated from stem cells of healthy and diseased (both active and quiescent UC) individuals results in decrease of LINE-1 (up to 8%) methylation level, when compared to tissue of origin and short-term cultures. Moreover, we revealed that LINE-1 methylation level in sub-cultured organoids decreases at different pace depending on the patient diagnosis (healthy control, active or quiescent UC). Therefore, we propose LINE-1 as a potential and convenient biomarker for reliable assessment of global methylation status of patient-derived intestinal epithelial organoids in routine testing of ex vivo cultures.